1991
DOI: 10.1002/pca.2800020303
|View full text |Cite
|
Sign up to set email alerts
|

A blind comparison of simple bench‐top bioassays and human tumour cell cytotoxicities as antitumor prescreens

Abstract: Simple bench‐top bioassays involving brine shrimp lethality, Lemna frond proliferation, and the inhibition of crown gall tumours on potato discs, as well as the human tumour cell lines A‐549 lung carcinoma, MCF‐7 breast carcinoma and HT‐29 colon adenocarcinoma, were compared for their accuracy to detect known in vivo (P‐388) active antitumour agents supplied by the National Cancer Institute. The potato disc assay was the best and showed excellent correlation to in vivo activity (p=0.008). The brine shrimp assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
2
15

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(158 citation statements)
references
References 21 publications
3
131
2
15
Order By: Relevance
“…However, all the extracts can still be considered safe due to their relatively high LD 50 . Anderson et al [20] . stated that extracts which showed LD5 0 higher than 100毺g/ml in the brine shrimp lethality test can be considered inactive and so safe for consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, all the extracts can still be considered safe due to their relatively high LD 50 . Anderson et al [20] . stated that extracts which showed LD5 0 higher than 100毺g/ml in the brine shrimp lethality test can be considered inactive and so safe for consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity assay was performed using the brine shrimp lethality test according to the method described in the literature [9]. Analysis of the data was performed by probit analysis on a Finney computer program to determine LC 50 (Biostat 2008; AnalystSoft, Vancouver, Canada).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…However, all the extracts can still be considered safe due to their high LD 50 values. Anderson et al [27] stated that extracts which showed LD 50 higher than 100 μg/mL in the brine shrimp lethality test can be considered inactive, and so safe for consumption. From the LD 50 values generated from their phytotoxic study, it also showed that all the extracts had high LD 50 , the implication of which is that they are non-toxic to the plant except at very high concentrations.…”
Section: Discussionmentioning
confidence: 99%